Comprehensive Management of Extensive Root Defect in Maxillary Molar Using Pre-Endodontic Build-Up and Adhesive Onlay: A Case Report - Steven Tanjung; Opik Taofik Hidayat (SONDE (Sound of Dentistry), 2026)
Background: Managing teeth with extensive root defects from secondary caries in failed restorations poses a significant clinical challenge, especially when restoration margins approach or extend beyond the gingival margin. Objective: To describe comprehensive endodontic and restorative management of a maxillary second molar with a severe root defect. Case Report: A 55-year-old woman presented with thermal sensitivity and a history of spontaneous radiating pain in the upper left posterior region. Clinical examination revealed a defective composite restoration with ICDAS 3, 2 root caries on tooth #17. Radiographs confirmed pulp involvement associated with an extensive defect on the distal surface of the root. The diagnosis was asymptomatic irreversible pulpitis with normal apical tissues. After local anesthesia and complete caries removal, a pre-endodontic build-up was performed using a sectional matrix system (Palodent® V3, Dentsply Sirona, USA) to reconstruct coronal walls and minimize contamination risk during root canal therapy. Biomechanical preparation was done with reciprocating NiTi instruments (Reciproc Blue®, VDW, Germany) followed by single-cone obturation with a bioceramic sealer. The final restoration was digitally designed using an intraoral scanner and CAD software. An indirect lithium disilicate adhesive onlay was selected to restore occlusal function. At follow-up, the tooth showed no symptomp and functionally stable. Conclusion: The integration of pre-endodontic build-up with indirect adhesive restoration offers a conservative and effective approach for managing posterior teeth with extensive root defects, preserving structural integrity and ensuring long-term clinical success.